DOI: 10.7190/shu-thesis-00131
|View full text |Cite
|
Sign up to set email alerts
|

Developing models of the small intestine

Abstract: Tissue engineering laboratory models of the small intestine. Tissue Engineering Part B, 24(2), 98-111. A schematic diagram illustrating the morphology of the small intestinal layers was chosen as the art cover for the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 242 publications
(470 reference statements)
0
7
0
Order By: Relevance
“…In addition, the group also demonstrated that the hydrogel could be used as a carrier for intestinal organoid transplantation in vivo. The intestinal organoids, which were transplanted with the PEG hydrogels, effectively improved colonic wound repair [42]. In addition, Capeling et al designed a simple hydrogel out of unmodified alginate, which served only as a simple physical scaffold for 3D intestinal organoid culture [15].…”
Section: Biomimetic Extracellular Matrices Based On Nanotechnologymentioning
confidence: 99%
“…In addition, the group also demonstrated that the hydrogel could be used as a carrier for intestinal organoid transplantation in vivo. The intestinal organoids, which were transplanted with the PEG hydrogels, effectively improved colonic wound repair [42]. In addition, Capeling et al designed a simple hydrogel out of unmodified alginate, which served only as a simple physical scaffold for 3D intestinal organoid culture [15].…”
Section: Biomimetic Extracellular Matrices Based On Nanotechnologymentioning
confidence: 99%
“…Therefore, the assessments in the next section should be treated somewhat speculatively and are derived from the overall military strategy, capabilities, and direction of development of the PLA, which regards global commons and transnational spaces, such as the poles, the deep sea, outer space, and cyberspace, as "new strategic frontiers" (战略新疆域) where great-power strategic competition is expected to be intense. 30 China's Goals in the North American Arctic China's overall foreign policy focuses on the realization of the "China Dream" of national rejuvenation, the recouping of supposedly "lost territories," such as Taiwan, various uninhabited maritime features in the East and South China seas, and sometimes territory in the presentday Russian Far East lost to Imperial Russia during the Qing Dynasty, as well as the establishment of a position of preeminence, first regionally, and then eventually globally. 31 In the course of China's quest for greater regional influence, PRC officials and authors tend to treat the United States and its network of alliances and partners, as well as the liberal international order they are embedded in and generally supportive of, as key obstacles to the accomplishment of China's ambitions.…”
Section: China's View Of the Arctic Generallymentioning
confidence: 99%
“…29 In Greenland, for the Citronen Fjord project, the China Nonferrous Metal Mining Group Company (CNMC) is partnering with Ironbark, an Australian mining firm. 30 Chinese mining activities in Alaska are much more limited than in Canada and Greenland. In 2009, CIC purchased a stake in Teck Resources, the parent company of the Red Dog Mine, which is focused on zinc mining.…”
Section: Miningmentioning
confidence: 99%
See 2 more Smart Citations